Sosialisasi Gerak Dasar Senam di SDN Teras dalam Kecamatan Tabunganen - Muhammad Abrar; Ulya Ridhani; Endang Pratiwi; Amalia Wahyuni; Ari Tri Fitrianto (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Gymnastics is a form of physical activity that combines gymnastic movements with musical rhythms to improve physical fitness, discipline, and teamwork. Socialization activities are carried out through the planning stage, material delivery, movement demonstrations, and direct practice by students. Basic movements in gymnastics are very important in efforts to instill the correct basic movements in movement. Basic movements The basic movements that are most popular are movements using objects or tools, commonly called basic manipulative movements. The results of the study showed that students were highly enthusiastic about participating in gymnastics, were able to understand and imitate the series of movements correctly, and showed increased coordination and cooperation. In addition, this activity contributed to instilling the values ​​of discipline, togetherness, and a spirit of physical fitness in the school environment. Thus, gymnastics socialization can be an alternative extracurricular activity that is beneficial for character development and student health.